2022
DOI: 10.1021/jacs.2c03544
|View full text |Cite
|
Sign up to set email alerts
|

A General Synthetic Method for High-Entropy Alloy Subnanometer Ribbons

Abstract: High-entropy alloys (HEAs) are attracting intensive attention due to their broad compositional tunability and interesting catalytic properties. However, precisely shaping the HEAs into suprathin low-dimensional nanostructures for achieving diverse applications remains an enormous challenge owing to their intrinsic thermodynamic instability. Herein we propose a new and general low-temperature method for incorporating up to eight metallic elements into one single-phase subnanometer ribbon to achieve the thinnest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(124 citation statements)
references
References 28 publications
2
122
0
Order By: Relevance
“…For example, McCormick et al demonstrated a multication exchange method to synthesize high-entropy metal sulfide NPs (ZnCoCuInGaS) from roxbyte CuS NPs . Tao et al reported HEA nanoribbons by coupling galvanic replacement of Ag nanowires with co-reduction, and our group demonstrated thermal conversion of colloidally prepared core@shell NPs to HEA NPs . Considering the latter, core@shell PdCu@PtNiCo NPs were prepared by seed-mediated co-reduction (SMCR).…”
Section: Introductionmentioning
confidence: 98%
“…For example, McCormick et al demonstrated a multication exchange method to synthesize high-entropy metal sulfide NPs (ZnCoCuInGaS) from roxbyte CuS NPs . Tao et al reported HEA nanoribbons by coupling galvanic replacement of Ag nanowires with co-reduction, and our group demonstrated thermal conversion of colloidally prepared core@shell NPs to HEA NPs . Considering the latter, core@shell PdCu@PtNiCo NPs were prepared by seed-mediated co-reduction (SMCR).…”
Section: Introductionmentioning
confidence: 98%
“…Cu(COOH) 2 was then reduced and precipitated on Pd ico seeds, resulting in the formation of Pd/Cu core/shell ico. 29 The high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and TEM were first employed to investigate the morphology and structure of Pd/Cu core/shell ico (feed ratio of Pd and Cu = 2.5:1). The Pd/Cu ico are fairly uniform in terms of size without any irregular nanoparticles (Figure S1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Then, Pd ico were dispersed in EG to mix with Cu­(COOH) 2 and ascorbic acid (AA). Cu­(COOH) 2 was then reduced and precipitated on Pd ico seeds, resulting in the formation of Pd/Cu core/shell ico . The high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and TEM were first employed to investigate the morphology and structure of Pd/Cu core/shell ico (feed ratio of Pd and Cu = 2.5:1).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, materials are regarded as high-entropy-alloy nanoparticles (HEANPs) when the number of metal components goes beyond 5. [6][7][8][9][10][11][12][13] The formation of a high entropy compound usually involves a kinetically controlled process, with stringent requirement on the precursor and temperature. 14,15 Metal-organic frameworks (MOFs) are porous crystals constructed by alternating arrangement of metal clusters and organic linkers, 16,17 standing as ideal precursors with atomic precision of the metal distribution.…”
mentioning
confidence: 99%
“…Typically, materials are regarded as high-entropy-alloy nanoparticles (HEANPs) when the number of metal components goes beyond 5. 6–13 The formation of a high entropy compound usually involves a kinetically controlled process, with stringent requirement on the precursor and temperature. 14,15…”
mentioning
confidence: 99%